2017
DOI: 10.1101/163030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Key role of piRNAs in telomeric chromatin maintenance and telomere nuclear positioning inDrosophilagermline

Abstract: Telomeric small RNAs related to PIWI-interacting RNAs (piRNAs) were discovered in different species, however, their role in germline-specific telomere function remains poorly understood. Using a Drosophila model, we show that the piRNA pathway provides a strong germline-specific mechanism of telomere homeostasis. We show that telomeric retrotransposon arrays belong to a unique class of dual-strand piRNA clusters whose transcripts, required for telomere elongation, serve simultaneously as piRNA precursors and t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 75 publications
(124 reference statements)
1
13
0
Order By: Relevance
“…Our observation that telomeres are longer in strains with terminal deficiencies suggests that subtelomeric sequences also regulate telomere elongation, consistent with previous studies [72][73][74].…”
Section: Host Regulation Of the Httssupporting
confidence: 92%
“…Our observation that telomeres are longer in strains with terminal deficiencies suggests that subtelomeric sequences also regulate telomere elongation, consistent with previous studies [72][73][74].…”
Section: Host Regulation Of the Httssupporting
confidence: 92%
“…Interestingly, we found that Het-A chromatin left nuclear peripheries upon loss of either Panx or dNxf2 (Extended Data Fig. 10) 20 . Transposon transcripts (I element) which are targeted by piRNAs have been previously shown to accumulate within nucleus 21 .…”
Section: Figurementioning
confidence: 79%
“… a , Density plots for dNxf2-Halo GoldCLIP reads from Mael knockdown OSCs (top panel), dNxf2-Halo GoldCLIP reads from LacZ knockdown OSCs (middle panel), and Panx co-immunoprecipitated smRNA reads (bottom panel, from previously published data 20 ) over the transposon consensus of mdg1. b and c are the same as in a except for gypsy ( b ) and 297 ( c ).…”
Section: Materials and Correspondencementioning
confidence: 99%
“…As mentioned above, Het-A, TART and TAHRE produce both sense and antisense transcripts [45,50,51]. Although Het-A and TART share common genomic niche, these elements exhibit also specific genetic requirements for their silencing and regulation [44,49,[91][92][93][94].…”
Section: Regulation Of Telomeric Transposition In the Germline: Piwi mentioning
confidence: 93%
“…piRNAs originate from genomic loci named 'piRNA clusters' [106]. HTT arrays represent specialized piRNA clusters, whose transcripts are both the piRNA precursors and their unique targets [91]. piRNA producing loci are characterized by a peculiar chromatin organization, enriched in H3K9me3 bound by the RDC complex formed by Rhino (Rhi, a paralogue of the heterochromatic protein HP1), Deadlock (Del), and Cutoff (Cuff) [107].…”
Section: Regulation Of Telomeric Transposition In the Germline: Piwi mentioning
confidence: 99%